Pengaruh Budaya Organisasi Terhadap Kinerja Melalui Komitmen Organisasi Dan OCB - Novitasari Novitasari; Eka Askafi; Nisa Mutiara (Universitas Islam Kadiri, 2022)
Human resources are seen as having an increasingly large role for the success of an organization, although at this time the rapid development of technology also affects the progress and success of a company (Anwar, 2021). OCB is a term used to identify employee behavior. The achievement of job satisfaction and OCB in employees are two aspects that are highly expected by the organization. Organizations that are able to make their employees have job satisfaction will produce employees who show a positive attitude towards their work. Organizational Citizenship Behavior (OCB) can arise from various factors in the organization, one of which is the existence of high organizational commitment from employees. The purpose of this study was to analyze the influence of Organizational Culture on Performance Through Organizational Commitment and Organizational Citizenship Behavior as Intervening Variables (Case Study of PT. Gudang Garam Tbk. Unit V). Data collection was carried out by distributing questionnaires to employees of PT. Gudang Garam Tbk. Unit V, either directly or indirectly. The population used is 115 employees consisting of four age groups, namely under 25 years, 25 years to 37 years, 38 years to 50 years, and above 50 years. Data analysis in this study used inferential data analysis, measurement model (outer model), structural model (inner model), descriptive statistical analysis model, path analysis method, hypothesis testing, mediation testing, and Sobel test. The results of this study indicate that organizational culture has a significant effect on the performance of employees of PT. Gudang Garam Tbk., Organizational culture is able to increase the organizational commitment of employees of PT. Gudang Garam Tbk., organizational culture has an influence on OCB, organizational commitment is not able to improve the performance of employees of PT. Gudang Garam Tbk., OCB acts as a partial mediation on employee performance, and organizational commitment does not act as a mediation on employee performance at PT. Gudang Garam Tbk. Units V.